Obesity, socio‐demographic and attitudinal factors associated with sugar‐sweetened beverage consumption: Australian evidence. (11th November 2015) - Pollard, Christina M.; Meng, Xingqiong; Hendrie, Gilly A.; Hendrie, Delia; Sullivan, Denise; Pratt, Iain S.; Kerr, Deborah A.; Scott, Jane A.
Abstract: Objective: To explore factors associated with sugar‐sweetened beverage (SSB) consumption in Australia. Methods: Pooled data from Western Australian (WA) and South Australian (SA) 2009 and 2012 nutrition monitoring survey series interviews of 2, 832 WA and 10, 764 SA adults aged 18 to 64 years. Demographic data were collected and independent samples t‐test, analysis of variance, multiple logistic regression performed. Results: Obese participants were more likely to consume SSB than healthy weight participants (SA: OR=1.77; 95% CI 1.56–2.02; WA: OR=1.53; 1.05–2.24). SA obese participants consumed more SSB per day (152.0 mL; 140.7–163.5) than healthy weight (80.1 mL; 73.2–88.2; p <0.001) and overweight participants (106.9 mL; 99.0, 114.8; p <0.001). Males were more likely to consume SSB than females (SA: OR 1.80; 1.35–2.40; WA: 1.81; 1.64–2.00). WA participants who didn't think about the healthiness of food (4.55; 2.71–7.64) and bought meals away from home the day prior (1.55; 1.15–2.09) were more likely to consume SSB. SA adults rating their health highest were less likely to consume SSB (0.62; 0.54–0.72). Conclusions: SSB consumers are more likely to be male, have little interest in health, or have purchased a meal away from home. Implications: Increasing awareness of the adverse health effects of consumption may be a first step in curbing SSB intake.